Projects as instruments of development administration: A qualified def ence and suggestions for improvement - Rondinelli, Dennis A. (Public Administration and Development, 1983)
Projects have become an important instrument of international assistan ce and of development administration because they seem to offer major advantages over other forms of planning and management. But projects h ave also come under increasing criticism in recent years. The benefits they offer to various interests involved in development ensure, howev er, that they are unlikely to be abandoned or to diminish in importanc e in the near future. Thus, ways must be found to make them more flexi ble and responsive methods of planning and managing social and human d evelopment activities. This can be done by planning, appraising and im plementing projects as policy experiments, making their design and adm inistration more learning-oriented, and using them as instruments of s trategic planning and management.